ANALISIS PENERAPAN ASUHAN FISIOTERAPI TERHADAP KUALITAS PELAYANAN FISIOTERAPI - Siti Munawarah (LLDIKTI Wilayah X, 2021)
Physiotherapy care for patients is a continuous and dynamic cycle process carried out byphysiotherapists who have the required competencies, integrated and coordinated with other relatedservices through medical records, information systems and effective communication systems. Thepurpose of the study was to analyze the application of physiotherapy care to the quality ofphysiotherapy services at Bukittinggi National Stroke Hospital and Achmad Mochtar BukittinggiHospital. The research method uses analyze method with a cross sectional design with a sample of 50people using accidental sampling technique. The results showed that the total score of the averageapplication of physiotherapy was 2.37 (not good) while the average score of physiotherapy servicequality was 2.86 (good). The results also illustrate the existence of physiotherapy relationship withphysiotherapy service quality with the results: assessment obtained p value (0.000), diagnosis with pvalue (0.028), intervention plan with p value (0.010), intervention with p value (0.000) evaluationwith p value (0.002) and documentation with p value (0.001). It can be concluded that the applicationof physiotherapy care in the services performed can affect the quality of hospital services. It isexpected that physiotherapy service officers can carry out work in accordance with establishedstandards